IDEOLOGI PENDIDIKAN DALAM PENANAMAN KETELADANAN GURU DI SMA IT YAPIRA - Indrawati, Dewi; Nadia, Teti; Laffanillah, Fani; Syifani, Fuzi; Hamdan Yasir, Muhammad; Najihudin, Ahmad; Dzulfikri, Muhammad (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2024)
This study explains the example of teachers who are very influential on the learning process of students of SMA IT YAPIRA BOGOR (1) teacher example, (2) teacher example, (3) teacher example, (3) teacher example, and (4) various teacher examples. This research uses a qualitative approach with the type of case study in schools. The subjects of the study are principals, teachers, and Student. Data collection techniques use observation and interview techniques, so the principal is oriented towards supportive behavior, teacher behavior that has will, sincerity / sincerity, and sincerity.